2010
DOI: 10.3109/08820538.2010.523671
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Use of Digital Imaging in Retinopathy of Prematurity Screening

Abstract: Retinopathy of prematurity (ROP) is a vision-threatening vasoproliferative condition of premature infants worldwide. As survival rates of younger and smaller infants improve, more babies are at risk for the development of ROP and blindness. Meanwhile, fewer ophthalmologists are available for bedside indirect ophthalmoscopy screening examinations. Remote digital imaging is a promising method with which to identify those infants with treatment-requiring or referral-warranted ROP quickly and accurately, and may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 27 publications
2
33
1
Order By: Relevance
“…The possibility of taking photographs or recording a video during the examination, and having a wider view of the retina are the main benefits of this method of examination. This has been confirmed in many studies, which have demonstrated the higher sensitivity of using the RetCam 3 digital system in comparison to the conventional technique of indirect ophthalmoscopy [9][10][11] . The aim of this paper is to describe a new modified technique for treating children with high-risk prethreshold ROP using the RetCam 3 digital imaging system -Camera-Assisted Laser photocoagulation and Cryotherapy of the Retina (CALCR).…”
Section: Introductionsupporting
confidence: 51%
“…The possibility of taking photographs or recording a video during the examination, and having a wider view of the retina are the main benefits of this method of examination. This has been confirmed in many studies, which have demonstrated the higher sensitivity of using the RetCam 3 digital system in comparison to the conventional technique of indirect ophthalmoscopy [9][10][11] . The aim of this paper is to describe a new modified technique for treating children with high-risk prethreshold ROP using the RetCam 3 digital imaging system -Camera-Assisted Laser photocoagulation and Cryotherapy of the Retina (CALCR).…”
Section: Introductionsupporting
confidence: 51%
“…Retcams present a cost-effective solution with which retinal images can be obtained by trained nonopthalmologists and evaluated by remote experts with high reliability and accuracy in detecting referral-warranted ROP. [24] Additionally, software that identifies infants at risk of developing severe ROP, such as WINROP, [25] a web-based screening tool developed at the University of Gothenburg in Sweden, which uses an algorithm based on serial weekly neonatal body weight measurements to support ROP risk prediction. Although the use of the software is currently free, limited staffing prevented us from exploring this tool.…”
Section: Researchmentioning
confidence: 99%
“…These results underscore the importance of accurate and highly sensitive retinal image detection practices which may be provided by a temporal evaluation technique. A number of retinal pathology assessments including choroidal nevus, 14 retinopathy of prematurity, 15 and retinal drusen 16 would likely show enhanced sensitivity in detection and progression monitoring with temporal image evaluation. Perhaps the greatest contribution of temporal image evaluation would be recognized through telemedicine or centralized image reading centers.…”
Section: Discussionmentioning
confidence: 99%